cUmar assurance of safety to the people of aelia and executive aspect of muslim concept of sovereignty - Aminurraasyid Yatiban; Fatimatuzzahra Abd Rahman (2012)
This paper attempts to investigate executive aspect of Muslim concept of sovereignty in light of a historical and remarkable document, namely cUmar Assurance of Amān (Safety) to the people of Aelia. This document was creatively initiated by cUmar al-Khattab (13-23 AH/ 634-644 CE), the second Muslim Caliph during the first Muslim conquest of Islamicjerusalem or also known as Aelia, purposely to determine future relationships among the people of the region. Since cUmar Assurance was in the heart of Muslim government during that time, it seems vital for the researcher to investigate how did cUmar implement executive aspect of Muslim sovereignty over the people of the ‘newly-conquered’ region of Aelia. Indeed, the executive body of the Muslim government represents an essential part within the societal affairs and organisation of the region. This paper also endeavours to examine the responses of local inhabitants to the new Muslim rulers. This is very exciting as the inhabitants of the region consist of multiracial and multireligious communities, namely Christians, Jews and others with Christians were still remaining the majority.